Exponential permutable semigroups - Ramani, Rushadije (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
A semigroup is called a permutable semigroup if is satisfied for all congruences and of . A semigroup is called an exponential semigroup if it satisfies the identity for every integer . In this paper we deal with permutable exponential semigroups. We describe the archimedian exponential semigroups and non-archimedian exponential semigroups which are semilattices of a group and a nilpotent semigroup.